Pemaknaan Puisi “Gadis Peminta-Minta” Karya Toto Sudarto Bachtiar melalui Pendekatan Semiotika dan Intertekstualitas - Siti Yulidhar Harunasari (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2016)
As homo semioticus humans communicate to others through signs, one of which is poem. And to understand these signs, we could use a certain method to get the meaning of the poem, or the message sent by the writer. Riffaterre said that a poem says one thing, and means another. It means that a poem speaks indirectly so that the use of its language is of a different form. The indirectness is produced by displacing, distorting, or creating meaning. The true meaning of a poem can be achieved through the two levels or stages of reading, i.e. heuristic reading and retroactive reading. Toto Sudarto Bachtiar sees poverty –as reflected by his poem, “Gadis Peminta-minta” –as the manifestation of God’s affection that must be passed with patience. The intertextuality between “Gadis Peminta-minta” and “Kepada Peminta-minta” written by Chairil Anwar as the hypogram can be seen from the major theme in common, that is how both of them see poverty.